Natrium Alginate and Graphene Nanoplatelets-Based Efficient Material for Resveratrol Delivery - Cristina Mormile; Ocsana Opriș; Stefano Bellucci; Ildiko Lung; Irina Kacso; Alexandru Turza; Adina Stegarescu; Septimiu Tripon; Maria-Loredana Soran; Ioana Bâldea (Gels)
In this study, alginate-based composite beads were developed for the delivery of resveratrol, a compound with therapeutic potential. Two formulations were prepared: one with sodium alginate and resveratrol (AR) and another incorporating graphene nanoplatelets (AGR) to improve drug release control. The beads were formed by exploiting alginate’s ability to gel via ionic cross-linking. For the AGR formulation, sodium alginate was dissolved in water, and graphene was dispersed in isopropyl alcohol to achieve smaller flakes. Resveratrol was dissolved in an ethanol/water mixture and added to the graphene dispersion; the resulting solution was mixed with the alginate one. For the AR formulation, the resveratrol solution was mixed directly with the alginate solution. Both formulations were introduced into a calcium chloride solution to form the beads. The release of resveratrol was studied in phosphate-buffered saline at different pH values. Results showed that the presence of graphene in the AGR sample increased drug release, particularly at pH 6.8, indicating a pH-driven release mechanism. Kinetic analysis revealed that the Higuchi model best describes the release mechanism. Finally, cytotoxicity tests showed the biocompatibility of the system in normal human cells. These findings suggest that graphene-enhanced alginate matrices have significant potential for controlled drug delivery applications.